Pengaruh Career Adaptability terhadap Kesiapan Kerja Mahasiswa pada Masa Pandemi - Putu Aninditha Veera Lakshmi; Kenny Elmartha (Jurnal Ilmu Perilaku, 2022)
The COVID-19 pandemic has had an impact on the high rate of unemployment, which may indicate the low level of work readiness especially for those who will enter the realm of work after completing their education. However, due to the limited research investigating this topic, the present study aimed to examine the effect of career adaptability on the work readiness of final year students during the pandemic. A total of 182 students were recruited through quota sampling to complete Career Adaptability and Work Readiness scales. The regression analysis results showed that career adaptability had a significant effect on work readiness. Career adaptability contributes 60% to the students’ work readiness. It indicates that career adaptability is an important aspect that must be possessed by students to develop their work readiness. Students with career adaptability have concerns about their future careers, so they would be better prepared to face the work conditions during pandemics.